Pemanfaatan Kascing untuk Menghambat Pertumbuhan Fusarium oxysporum pada Tanaman Tomat - Susanna Susanna; M. Abduh Ulim; Junaidi Junaidi (Jurnal Agrista, 2009)
The Use of Vermicompost (Kascing) to Inhibit the development of Fusarium oxysporum on Tomato PlantsABSTRACT. Fusarium wilt disease caused by Fusarium oxysporum f. sp. lycopersici is the one of important disease on tomato plant. The use of fungicides can give a negative impact on this environment. Currently, control methods that are environmentally friendly began to be developed again, one of which the use of organic fertilizer vermicompost (kascing). The objective of research was to study effectiveness of kascing to control F. oxysporum on tomato plant. The experiment applied a completely randomized design with 4 replications. The dosage of vermicompost studied consisted of 6 levels, i.e.: 0 g, 50 g, 100 g, 150 g, 200g, and 250 g of vermicompost. The result showed that the dosage of vermicompost significantly affected of incubation period of F. oxysporum f.sp. licopersici, the height of plant oat 30 days after planting (DAT), percentage of the wilt plant, the length of xylem discoloration, and weight of fruits. The best dosage of vermicompost is 150 g polibag-1.